ANALISIS PENGARUH UPAH MINIMUM DAN PENGANGGURAN TERHADAP KEMISKINAN SERTA DAMPAKNYA PADA PERTUMBUHAN EKONOMI DI PROVINSI JAMBI - RIA REPA SUSANA, SUPRIHATIN LESTARI (Al-Mizan: Jurnal Ekonomi Syariah, 2021)
The purpose of this study was to determine how the influence of minimum wagesand unemployment on poverty and their impact on economic growth in Jambiprovince. The method used is a quantitative research method using statistical pathanalysis (path analysis). Data collection uses secondary data, sourced from theofficial website of the Financial Services Authority (OJK), the Central StatisticsAgency (BPS), Bank Indonesia (BI) and research journals and e-books. The datacollected is in the form of data every year, then the writer arranges the time seriesof annual data. The data was processed using the IBM SPSS Statistic 26application. The results showed that the direct effect of minimum wage andunemployment on poverty had no significant effect. The direct effect of minimumwage and unemployment on economic growth has a significant direct effect onpoverty. Minimum wages and unemployment through poverty affect economicgrowth by 77.6% and the remaining 22.4% is obtained by other variables notincluded in this study.